Recurrent Wheezing in Pre-school Age: Not Only Airway Reactivity! - Roversi, Marco; Porcaro, Federica; Francalanci, Paola; Carotti, Adriano; Cutrera, Renato (Frontiers in Pediatrics, 2020)
Background: About a fifth of all mediastinal masses are primary cysts arising in the absence of other underlying pathology. Bronchogenic cysts, although rare, are the most frequent type responsible for lower airways compression as they often develop in the peripheral branches of the tracheobronchial tree. Case presentation: We report the case of a 6-months-old child admitted for acute respiratory distress and wheezing not responsive to asthma treatment. Digestive and airway endoscopy proved a mild and a marked reduction of the esophageal and tracheal lumen, respectively. The nocturnal polygraphy showed an underlying obstructive disorder and the chest CT scan confirmed the presence of a wide mediastinal cyst compressing the trachea. The mass, later identified as a bronchogenic cyst, was surgically removed with complete resolution of the patient's respiratory symptoms. Discussion: Our case shows that differential diagnosis of wheezing in pre-school aged children should encompass causes others than airway reactivity, thus prompting further evaluation and management.